Trade-offs in the value capture of architectural firms: the significance of professional value - Bos -de Vos, Marina; Wamelink, Hans; Volker, Leentje (A+BE | Architecture and the Built Environment, 2018)
Architectural firms often have difficulty generating profit from their services as they pursue not only commercial but also professional goals. These goals frequently conflict and have to be balanced during the process of value creation and value capture. So far, literature has focused on the interaction between the perceived use value for the customer and the fee that is paid to the firm. To better understand how professional service firms realize their organizational targets, professional value needs to be included. In this study, in-depth interviews with the architects and clients of nine housing projects provide insight into the content and process of value capture by architectural firms. The data reveal strategies by which architects tried to maximize the capture of professional value at the expense of profit or sometimes even their clients’ perceived use value. These trade-offs in value capture confirm the importance of professional value when studying value creation and capture in a professional service context. This paper provides an understanding of how architectural firms struggle to balance competing goals and highlights the importance of well-managed value capture.